THE TRANSPORT GLIDER - Alexander, McGill (Scientia Militaria - South African Journal of Military Studies, 2012)
During the Second World War airborne ground forces were employed for the first time in a major conflict, and on a scale never subsequently equalled. These soldiers and their equipment were delivered on or neartheir objectives in three ways, viz by parachute, by glider and by powered aircraft landing on captured airfields.